La gouvernance des espaces protégés: vers un partage de la nature ? - Céline Chadenas; Vincent Andreu-Boussut; Celine Barthon; Xavier Michel; Arnaud de Lajartre (VertigO)
for thirty years and the setting aside of natural environments on the French coasts of the Atlantic, the Channel and the Mediterranean, their opening to the public has led to a development of space, sometimes reducing itself to a few discovery trails, going, for other sites, to participate fully in the tourist dynamic of the contiguous territory. Environmental pedagogy is the main pretext for the development of these sites for the public, but these practices have contributed to the zonation of space. It becomes all the more essential as the pressure exerted around or even inside the perimeter of protection is perceived as important, driven by a very strong craze for activities in nature. This zoning gives the impression of loosening binding protection status towards more integrated and shared forms of management and governance. However, the observation of the disturbance of the species sometimes leads the manager to move towards a new zonation of the protected area, by creating sanctuaries of a more restrictive nature, also justifying a return to a more limited opening of these spaces for the general public or aiming, in some cases, for the total closure of a site. This article proposes to analyze the way in which the division of the space of three natural reserves of metropolitan France, the Bay of Somme (Picardy), Saint Lucia (Aude) and Moëze-Oléron (Charente-Maritime) was organized. The trajectories of these sites will be apprehended, from the creation of the protected space until today, observing in particular the dialectics opening / closing and permanence / rupture that these places know and the way in which they are apprehended. More broadly, the objective of this article is to identify models for sharing space in order to understand how natural reserves can contribute to the sustainable development of the territories in which they are integrated, the protection of biodiversity, thus becoming the revealer of a new space dynamic.